Status of echocardiography in clinical cardiology - Riecanský, I (Cor et vasa, 1988)
Echocardiography (ECHO) is at present the most important and most useful non-invasive diagnostic method employed in cardiology. Its dominant position is the result of dramatic development of its technology and methodology enabling a wide range of clinical applications. Apart from M-mode and two-dimensional ECHO, these methods include mainly Doppler ECHO (pulse and continuous, colour), computer, contrast, exertional, transoesophageal ECHO, ultrasound characteristics of tissue (textural analysis). Moreover, technical improvements have enabled to quantify, standardise and unify ECHO measurements and nomenclature. The most general contribution of ECHO to present-day clinical cardiology lies in the confirmation or exclusion of a suspected cardiovascular disease and assessment of the degree of circulatory system involvement.
Keywords: echokardiografie; Humans; lidé; Heart Diseases; Echocardiography; nemoci srdce